The Cohesion of Paragraph in Research Proposal of XI Graders of Kebon Dalem Senior High School Semarang - Pawarta, Edmandus Hari; Santoso, Bernadus Wahyudi Joko (Pascasarjana Universitas Negeri Semarang, 2019)
Knowledge about cohesive devices are important to be masterd by students in composing coherent paragraph. The research has purpose to analyze the coherence of a paragraph in discourse of research proposal of XI graders of SHS. The data of the research is excerpt of research proposal discourse text composed by the students of Kebon Dalem SHS Semarang. Other data source are fifty four proposals. The data were collected by using reading and noting techniques. The data analysis was done by using distributive method. Theoretical approach used are discourse theory of Halliday and Hasan. The methodological approach used was descriptive qualitative. The analyzed data is presented in the form of description of cohesive device facility used to realize coherence of the paragraph. The findings showed the realization of lexical cohesion among sentences are repetition, synonymous, and hyponym. Besides that, the realization of grammatical cohesion among sentences are reference, substitution, conjunction, and nominalization. Meanwhile, the realization of cohesive devices among paragraphs are repetition, reference, and conjunction. It is expected that the result of this research can be used for developing the learning-teaching of research proposal writing skills.